A Case Study of Joint Forest Management in Andhra Pradesh - Mukherji, S. D. (Indian Forester, 2000)
Based on the 1988 National Forest Policy, the Joint Forest Management(JFM) Programme has been taken up in different States. Andhra Pradesh is one the leading States implementing JFM over 16.51akh hectares by forming 6,575 Van a Samarakhshana Samities (VSS). The case study of oqe VSS in Vizianagram District (Andhra Pradesh) has been presented to show how the people and the forests have benefitted from the JFM Programme. The paper also deals with the difficulties in funding the Programme and it is suggested that JFM should be taken up under poverty alleviation programmes of the Rural Development Department. In tribal areas, JFM should be considered as one of the strategies for developing the tribal economy instead of depending upon agriculture alone.